2014
DOI: 10.1016/j.str.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of an Intrinsically Disordered Segment in Ets1 Shifts Conformational Sampling toward Binding-Competent Substates

Abstract: Functions of many proteins are affected by posttranslational modifications of intrinsically disordered (ID) regions, yet little is known about the underlying molecular mechanisms. By combining molecular dynamics simulations and protein docking, we demonstrate that the addition of phosphates to an ID segment adjacent to the PNT domain of Ets1 directs conformational sampling toward substates that are most compatible with high-affinity binding of the TAZ1 domain of its coactivator CBP. The phosphate charges disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“… 24 ), Cdc25A and Cdc25B phosphatases 25 26 . In a recent molecular dynamics study, it was also shown that phosphorylation of a disordered segment shifts the conformational equilibrium towards binding competent sub-states 27 .…”
Section: Resultsmentioning
confidence: 98%
“… 24 ), Cdc25A and Cdc25B phosphatases 25 26 . In a recent molecular dynamics study, it was also shown that phosphorylation of a disordered segment shifts the conformational equilibrium towards binding competent sub-states 27 .…”
Section: Resultsmentioning
confidence: 98%
“…The literature reports many exceptions to the PPII target for SH3-domain interaction, such as 3 10 -helices, but these structures were observed by X-ray crystallography of peptide-SH3-domain complexes that were better-behaved than the one studied here [ 27 , 36 , 72 ]. We consider that a more realistic scenario here is that MBP samples a variety of conformations within the SH3-domain pocket, and that these are modulated by post-translational modifications, such as phosphorylation by MAPKs at T92 and T95 [ 8 , 73 ]. Although it was expected here that the proline-rich segment of this IDP would form a PPII conformation [ 41 ], there are exceptions to this model [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation in disordered regions can modulate local conformational preferences such that bound-state-like pre-structuring is observed (81). Thus, priming modifications in disordered regions can serve to achieve specificity for E3 recognition, using a signaling event as a trigger and thereby achieving temporal and signal-dependent binding specificity.…”
Section: Disordered Primary Degrons Are Regulated By Ptms Within Degrmentioning
confidence: 99%